Understanding trade-offs and synergies among soil functions to support decision-making for sustainable cultivated land use - Zhao, Rui; Gabriel, Jose Luis; Rodríguez Martín, Jose Antonio; Feng, Zhe; Wu, Kening (Frontiers in Environmental Science, 2022)
Soil provides a diverse and complex range of ecosystem services. Understanding the trade-offs and synergies among soil functions is foundational for effective soil ecosystem management and human well-being. In contrast, the long-term pursuit of solely productive functions in cultivated land use has resulted in soil degradation and weakened other ecological functions. This study collected soil, topographic landform, climate, and management data from 151 fields in four counties and three climatic zones in China. The Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model was used to evaluate nutrient retention, water production, and carbon storage, and the market value method was used to evaluate the value of the soil production function. A semi-quantitative model of Bayesian belief networks (BBNs) was used to simulate soil processes, thus revealing factors potentially influencing the supply capacity of five soil functions. Sensitivity analysis was used to identify the key variables influencing soil functional supply, and the probabilistic inference was used to identify interactions among soil's multiple functions. The main findings were as follows: (i) In four counties, the spatial heterogeneity in the supply of the five soil functions was relatively high. (ii) The primary variables influencing the supply of soil's multiple functions were climatic conditions, management level, carbon storage, soil nutrients, soil biology, soil structure, and topography. (iii) Trade-offs existed among primary productivity (PP), water purification and regulation (WPR), and carbon sequestration and regulation (CSR). Moreover, the provision of functional and intrinsic biodiversity (PFIB), WPR, and CSR were synergistic; specifically, the CSR and WPR services synergized with the nutrient provision and cycling (PCN). This research may aid in understanding the supply of, and interactions among soil's multiple functions, thus aiding in using BBNs to analyze soil ecosystem services. In addition, this study may provide a reference for management decision-making to maximize the overall benefits of soil functions in cultivated land use.